Desenvolvimento econômico e distribuição de renda: enfoque sobre as causas do subdesenvolvimento brasileiro - Rodrigues, Raquel Nair (2017)
The present research uses the analysis of recognized authors, to address the poor distribution of income in Brazil from the perspective of its structural constraints, particularly, it sought to point to technological dependence as the main determinant of inequality. It is argued that without the ownership technology, the internal market would tend to turn more and more towards the richer top of the population. In this model, only the highest income layer would be able to give continuity to capital accumulation. Thus, the National Development Plans while adopting economic growth policies, not changing the exogenous nature of technical transformations, referred to in the model, only reinforced underdevelopment. In addition, it is pointed out that this mode of accumulation implies overexploitation of labor. In rescuing the conclusions drawn by the pioneers in the underdevelopment, study, its causes and consequences, it is intended to contribute to bring the subject up for debate